A Social Phenomenon and Conflict of The Character: A Marxism Analysis on Freedom Writers Movie - Intan safitri; Faishal Arkan (Journalistics: Journal of English Teaching and Applied Linguistics, 2021)
The conflict theory has been used to explain a wide range of social phenomena, including wars and revolutions, wealth and poverty, discrimination and domestic violence. It ascribes most of the fundamental developments in human history, such as democracy and civil rights, to capitalistic attempts to control the masses rather than to a desire for social order. The theory revolves around concepts of social inequality in the division of resources and focuses on the conflicts that exist between classes.focused on the conflict between two primary classes. The bourgeoisie represents the members of society who hold the majority of the wealth and means. The proletariat includes those considered working class or poor. With the rise of capitalism, Marx theorized that the bourgeoisie, a minority within the population, would use their influence to oppress the proletariat, the majority class.The uneven distribution within the conflict theory was predicted to be maintained through ideological coercion where the bourgeoisie would force acceptance of the current conditions by the proletariat. Marx further believed that as the working class and poor were subjected to worsening conditions, a collective consciousness would bring the inequality to light and potentially result in revolt. If conditions were subsequently adjusted to address the concerns of the proletariat, the conflict circle would eventually repeat.